1983
DOI: 10.1113/jphysiol.1983.sp014667
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical response to noradrenaline in calcium‐free solution in the rat vas deferens.

Abstract: SUMMARY1. Mechanical responses to noradrenaline (NA) were investigated in the rat vas deferens exposed to Ca-free solution containing 0.5 mM-EGTA. A tonic response was produced in Ca-free solution at the epididymal portion, while almost no response could be observed at the prostatic portion.2. In most experiments NA (10-4 M) was applied for 4 min, every 20 min. The absolute tension development in Ca-free solution was usually 60-80 %0 of the control tonic response in the presence of 2-4 mM-Ca. The response coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 20 publications
2
30
0
Order By: Relevance
“…The rhythmic activity induced in the rat vas deferens by B25 appeared to be very similar to the contractile effect obtained in this preparation with different compounds (Hay & Wadsworth, 1979;Ashoori & Tomita, 1983;Mishra et al, 1988). In these reports the effects of some procedures affecting calcium translocation indicate that rhythmic contractions were highly dependent upon the activation of VSCC in the membrane.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The rhythmic activity induced in the rat vas deferens by B25 appeared to be very similar to the contractile effect obtained in this preparation with different compounds (Hay & Wadsworth, 1979;Ashoori & Tomita, 1983;Mishra et al, 1988). In these reports the effects of some procedures affecting calcium translocation indicate that rhythmic contractions were highly dependent upon the activation of VSCC in the membrane.…”
Section: Discussionmentioning
confidence: 60%
“…Regardless of what agonist has been used, this rhythmic activity has proved to be closely dependent upon external calcium since it was completely prevented in CaCl2-free Krebs solutions (Ashoori & Tomita, 1983;Hay & Wadsworth, 1979;. More recently Langton & Huddard (1987) have shown that in the rat vas deferens, the rhythmic activity induced by slight depolarizing KCI solutions could be selectively mediated by rapidly inactivating voltage-sensitive calcium channels (VSCC) in the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that, during maintained contractions, Ca2+ is mobilized by neurotransmitters from an intracellular pool which may be different from that responsible for the initial transient contraction (Heaslip & Rahwan, 1982;Ashoori & Tomita, 1983) whereas Casteels et al, (1981) envisaged the possibility that noradrenaline could also affect the contractile proteins by a mechanism which does not include a change in cytoplasmic Ca2+ concentration.…”
Section: Introductionmentioning
confidence: 99%
“…In respect to the latter, it may be stressed that the amplitude of agonist-induced contractions increases progressively by prolonged exposure to Ca-free solution for longer than 20 h in the cases of vas deferens (ASHOORI and ToMITA , 1983), rat myometrium (ASHOORI et al, 1985), and guinea pig stomach (ASHOORI et al ., 1986). Progressive increase of the ATP-induced contraction due to prolonged exposure to Ca-free solution is also indicated in the present experiment (Figs .…”
Section: Resultsmentioning
confidence: 99%
“…EGTA-resistant contraction. Contractions can be evoked in Ca-free media in various smooth muscle tissues including blood vessels, vas deferens , and stomach (DETH and VAN BREEMEN, 1977;CASTEELS et al, 1981;ASHOORI and TOMITA, 1983;ITOH et al, 1983;BOND et al, 1984;AsxooRl et al, 1986), when agonists are applied . Such contractions are also shown to occur in myometrial smooth muscle (see introduction for references).…”
Section: Resultsmentioning
confidence: 99%